2022
DOI: 10.3389/fendo.2022.891088
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Lumber Disc Degeneration With Paraspinal Muscles Myosteatosis in Discogenic Low Back Pain

Abstract: Accompanied with intervertebral disc (IVD) degeneration, increasing fat infiltration of paraspinal muscles may be related to discogenic low back pain (DLBP), but their relationship is still unclear and the classical animal models are not completely applicable. The purpose of this study was to assess the paraspinal muscle fat infiltration in patients with DLBP by quantitative MRI, and to develop a novel DLBP rat model to explore the potential relationship between DLBP paraspinal muscle fat infiltration and TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Recently, advanced chemical shift-encoded MRI (CSE-MRI) has been reported to have the advantages of convenient measurement, short scanning time, accurate quantification, and good reproducibility, and can comprehensively evaluate fat content in the organs by proton density fat fraction (PDFF) 18 . Moreover, PDFF based on CSE-MRI technology has been confirmed to be in good agreement with MRS and histology 19 , and has been considered a reliable biomarker for non-invasive fat quantification 20 . Kromrey et al 21 found an inverse correlation between pancreatic steatosis quantified by PDFF and impaired pancreatic exocrine function.…”
Section: T1wimentioning
confidence: 88%
“…Recently, advanced chemical shift-encoded MRI (CSE-MRI) has been reported to have the advantages of convenient measurement, short scanning time, accurate quantification, and good reproducibility, and can comprehensively evaluate fat content in the organs by proton density fat fraction (PDFF) 18 . Moreover, PDFF based on CSE-MRI technology has been confirmed to be in good agreement with MRS and histology 19 , and has been considered a reliable biomarker for non-invasive fat quantification 20 . Kromrey et al 21 found an inverse correlation between pancreatic steatosis quantified by PDFF and impaired pancreatic exocrine function.…”
Section: T1wimentioning
confidence: 88%
“…By quantitative MRI, Huang et al. ( 38 ) assessed fat infiltration in PSMs of patients with discogenic LBP and rats in a novel discogenic LBP model. It was found that fatty infiltration was present in the PSMs of both LBP patients and rats and that there was a causal relationship between fatty infiltration and IVDD ( 38 ).…”
Section: Fatty Infiltration In Psmsmentioning
confidence: 99%
“…( 38 ) assessed fat infiltration in PSMs of patients with discogenic LBP and rats in a novel discogenic LBP model. It was found that fatty infiltration was present in the PSMs of both LBP patients and rats and that there was a causal relationship between fatty infiltration and IVDD ( 38 ). Another study showed that dogs with higher IVDD grades had less fat infiltration in psoas and multifidus than those with lower mean IVDD degrees ( 39 ).…”
Section: Fatty Infiltration In Psmsmentioning
confidence: 99%
See 1 more Smart Citation
“…He also performed a parallel analysis in humans with discogenic Low Back Pain, through MRI images. After analyzing the two groups, it was concluded that there is a causal relationship between fatty infiltration of the musculature and discogenic pain [14].…”
Section: Introductionmentioning
confidence: 99%